1992
DOI: 10.1002/aja.1001940308
|View full text |Cite
|
Sign up to set email alerts
|

Development of olfactory nerve glia defined by a monoclonal antibody specific for schwann cells

Abstract: Although there is considerable interest in the possible role of olfactory glia in the pathfinding abilities of olfactory nerve axons, the complete development of these glia in vivo has not been described. Using a specific Schwann cell marker, the 1E8 antibody, we have found that olfactory nerve glia can be identified throughout development. These glia appear to originate in the olfactory placode and migrate initially into the periphery of the olfactory nerve, and later into the center of the nerve. Olfactory n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 40 publications
(61 reference statements)
4
33
0
1
Order By: Relevance
“…Heterotopic grafts further showed that hindbrain-and spinal cord-derived NCCs can form OECs. We also identified Sox10 as a molecular marker for OECs: this is consistent both with the maintenance of Sox10 expression in all NCC-derived glia (23) and with the fact that Sox10 directly regulates the "myelin" P0 gene (24), an OEC marker in chick and rat (22,25,27 YFP embryos, in which NCCs are permanently labeled genetically (32,33), yielded results entirely consistent with our fate-mapping experiments in avian embryos. Hence, OECs are derived from the neural crest, not from the olfactory placodes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Heterotopic grafts further showed that hindbrain-and spinal cord-derived NCCs can form OECs. We also identified Sox10 as a molecular marker for OECs: this is consistent both with the maintenance of Sox10 expression in all NCC-derived glia (23) and with the fact that Sox10 directly regulates the "myelin" P0 gene (24), an OEC marker in chick and rat (22,25,27 YFP embryos, in which NCCs are permanently labeled genetically (32,33), yielded results entirely consistent with our fate-mapping experiments in avian embryos. Hence, OECs are derived from the neural crest, not from the olfactory placodes.…”
Section: Discussionsupporting
confidence: 75%
“…2 C and D; n = 9/9), which is expressed in migrating NCCs and required for the differentiation of NCC-derived glia (23). Sox10 also directly regulates expression of the "myelin" P0 gene (24), a marker for chick and rat OECs (22)(23)(24)(25)(26) as well as for migrating NCCs and their glial derivatives (26,27). Many of the GFP chick NCCs and their processes on the olfactory nerve at E6.5 expressed the OEC marker P0 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This capacity is thought to be due in part to the unique glial cells of the olfactory nerve, known as olfactory ensheathing cells (ECs). These cells share phenotypic characteristics in common with Schwann cells and astrocytes [5,15,41,47] but are unique in that they can cross the transitional zone between the peripheral nervous system and CNS [17,45]. Although it is well documented that ECs express extracel lular matrix molecules such as N-CAM and laminin [22,33] that could contribute to axonal growth, few studies 204 E. Woodhall et al f Molecular Brain Research 88 (2001) [203][204][205][206][207][208][209][210][211][212][213] have shown unequivocal direct evidence that ECs syn thesize and secrete growth factors [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in early mouse embryos that cells migrating from the medial side of the olfactory placode contain luteinizing hormone-releasing hormone (LHRH) and these cells eventually take up residence in the hypothalamus (Schwanzel-Fukuda and Pfaff, 1989;Wray et al, 1989). Other migrating cells become olfactory Schwann cells (OSCs) and some of them eventually distribute in the outer nerve layer of the olfactory bulb (OB) (Doucette, 1989;Chuah and Au, 199 1;Norgren et al, 1992).…”
mentioning
confidence: 99%